2020
DOI: 10.3390/ijerph17062120
|View full text |Cite
|
Sign up to set email alerts
|

Examining Body Satisfaction and Emotional–Social Intelligence among School Children: Educational Implications

Abstract: In childhood, the perception of body image is in the construction phase and emerges linked to the aesthetic ideals of society, which is well differentiated according to gender. In this way, according to people’s interpretations of the environment and how to manage it emotionally, greater or lesser body satisfaction may be generated, which could have irreversible consequences for children. Therefore, our interest lies in how body image satisfaction and gender can act as modulating variables of emotional intelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The remaining 47 articles were evaluated for inclusion by reviewing their full text and resulted in the exclusion of 38 records for the following reasons: (1) they did not employ cross-sectional/cohort studies ( n = 5), (2) EI was not a predictor ( n = 11) or (3) participants had a mean age of ≥18 years ( n = 22). Finally, 9 articles [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] were included in the systematic mapping review ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 47 articles were evaluated for inclusion by reviewing their full text and resulted in the exclusion of 38 records for the following reasons: (1) they did not employ cross-sectional/cohort studies ( n = 5), (2) EI was not a predictor ( n = 11) or (3) participants had a mean age of ≥18 years ( n = 22). Finally, 9 articles [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] were included in the systematic mapping review ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A description of the included studies is reported in Table 1 . The included articles were published between 2007 [ 35 ] and 2020 [ 34 , 38 ] in China [ 39 , 40 ], Spain [ 34 , 42 ], Germany [ 38 ], France [ 36 ], Mexico [ 41 ], Taiwan [ 37 ] and the United States [ 35 ]. All studies employed a cross-sectional design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has emphasized the contribution made by physical activity and the positive role it can play on students' IE [36][37][38], specifically, through engagement in organized sport [39] and body image satisfaction [40]. PE classes can promote the development of students' EI [41], and CL could be a useful methodological tool to do it because of the structural elements that it includes. Previously reported studies in educational contexts have shown that adequate EI in group members can lead them to develop greater levels of positive interdependence and promotive interaction [32].…”
Section: Introductionmentioning
confidence: 99%